Thymic epithelial cells are a nonredundant source of Wnt ligands for thymus development - Brunk, Fabian Ludwig; Augustin, Iris; Boutros, Michael (The journal of immunology, 2015)
Wnt signaling has been implicated in T cell development. However, it remained unclear which cell type is the major source of Wnt ligands and to what extent thymic epithelial cell (TEC) development is dependent on Wnt signaling. In this study, we analyzed the role of Wnt ligands provided by TECs for the development of T cells and TECs without manipulating the intracellular Wnt signaling machinery in either cell type. To this end, we used conditional knockout mice (FoxN1-Gpr177) in which TECs are unable to secrete Wnt ligands. Gpr177 (Evi/Wls) is a Wnt-specific cargo receptor that is required for the secretion of Wnt ligands. We found that TECs are the main source of Wnt ligands in the thymus, which serves a nonredundant role, and lack of TEC-provided Wnt ligands led to thymic hypotrophy, as well as a reduced peripheral T cell pool. Despite being reduced in numbers, T cells that developed in the absence of TEC-secreted Wnt ligands were functionally competent, and the subset composition of the peripheral T cell pool was not affected. Thus, our data suggest that T cell development is not directly dependent on TEC-provided Wnt ligands. Rather, TEC-secreted Wnt ligands are essential for normal thymus development and normal peripheral T cell frequencies but are dispensable for T cell function in the periphery.